2009
DOI: 10.1242/dev.026054
|View full text |Cite
|
Sign up to set email alerts
|

Fasciclin 2, theDrosophilaorthologue of neural cell-adhesion molecule, inhibits EGF receptor signalling

Abstract: Adhesion proteins not only control the degree to which cells adhere to each other but are increasingly recognised as regulators of intercellular signalling. Using genetic screening in Drosophila, we have identified Fasciclin 2 (Fas2), the Drosophila orthologue of neural cell adhesion molecule (NCAM), as a physiologically significant and specific inhibitor of epidermal growth factor receptor (EGFR) signalling in development. We find that loss of fas2 genetically interacts with multiple genetic conditions that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 48 publications
5
55
0
Order By: Relevance
“…Several mechanisms have been shown to regulate EGFR signaling, including negative regulators, extracellular matrix proteins and coreceptors (Boisclair Lachance et al, 2009;Mao and Freeman, 2009;Wang et al, 2008;Zartman et al, 2009). It will be important to determine whether trans-acting elements can provide further local regulation of EGFR signaling to increase the robustness of DR formation through anchoring GRK along its entire path without affecting the dorsal-ventral axis of the fly.…”
Section: Willistoni Grk Rescues D Melanogaster Grk-null Flies Andmentioning
confidence: 99%
“…Several mechanisms have been shown to regulate EGFR signaling, including negative regulators, extracellular matrix proteins and coreceptors (Boisclair Lachance et al, 2009;Mao and Freeman, 2009;Wang et al, 2008;Zartman et al, 2009). It will be important to determine whether trans-acting elements can provide further local regulation of EGFR signaling to increase the robustness of DR formation through anchoring GRK along its entire path without affecting the dorsal-ventral axis of the fly.…”
Section: Willistoni Grk Rescues D Melanogaster Grk-null Flies Andmentioning
confidence: 99%
“…It is believed that in adult NMJs it is accumulated in the synaptic periactive zone where it functions as a homophilic cell adhesion molecule (Ashley et al, 2005;Marie et al, 2004;Schuster et al, 1996;Kristiansen and Hortsch, 2008;Mao and Freeman, 2009). Immunofluorescence revealed that the Fas II immunoreactivity is not precisely co-localized with another component of the Star marks a silver enhanced gold particle signaling for CSP.…”
Section: Resultsmentioning
confidence: 99%
“…Fasciclin II represents the structural and functional ortholog of the vertebrate NCAM (Kristiansen and Hortsch, 2008;Mao and Freeman, 2009). It is believed that in adult NMJs it is accumulated in the synaptic periactive zone where it functions as a homophilic cell adhesion molecule (Ashley et al, 2005;Marie et al, 2004;Schuster et al, 1996;Kristiansen and Hortsch, 2008;Mao and Freeman, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2), consistent with the misoriented ommatidia observed in vav pupal retinas. Rotation defects and extra cells (including R7s) are also found in mutants for negative regulators of EGFR signalling, such as Sprouty and FasII (Casci et al, 1999;Mao and Freeman, 2009), as well as upon expression of dominant activators of EGFR pathway (Brunner et al, 1994;Strutt and Strutt, 2003). Thus, even though Vav has been so far shown to act positively downstream of the EGFR pathway, vav retina phenotypes are reminiscent of EGFR hyperactivity, suggesting that Vav has a new role as a negative regulator of EGFR signalling.…”
Section: Vav Is a Negative Regulator Of The Egfr Signalling Pathwaymentioning
confidence: 99%